Determination of remifentanil in neonatal dried blood spots by liquid chromatography-tandem mass spectrometry - Trontelj Jurij; Rozman Aleš; Mrhar Aleš (Acta Pharmaceutica)
Remifentanil is an ultra-short-acting synthetic opioid-class analgesic which might be increasingly used “off-label” as pain management during labour. Side effects in parturients during labour, and in the infant at birth are of particular concern, especially respiratory depression which is concentration-dependent, and can occur at levels as low as 3–5 ng mL–1. The safety of such use, particularly in newborns due to remifentanil placental transfer, has not been fully demonstrated yet, partly due to the lack of a suitable non-invasive analytical method. The aim of our work was to develop a sensitive method to monitor the levels of remifentanil in neonates by a non-invasive sampling of umbi lical cord blood to support efficacy and safety trials. The presented LC-MS method is sensitive enough to reliably quantify remifentanil in just 20 µL of blood at only 0.3 ng mL–1. The dried blood spot sample preparation included solvent extraction with subsequent solid-phase extraction. The method was validated in terms of accuracy, precision, recovery, matrix effect, and stability, and was successfully applied to a small pilot study. The estimated arterial blood concentrations at the time of delivery ranged from 0.2 to 0.3, and up to 0.9 ng mL–1 in neonatal, and maternal samples, respectively.